Dynamic chromosomal interactions and control of heterochromatin positioning by Ki‐67. (17th October 2022) - van Schaik, Tom; Manzo, Stefano G; Vouzas, Athanasios E; Liu, Ning Qing; Teunissen, Hans; de Wit, Elzo; Gilbert, David M; van Steensel, Bas
Abstract: Ki‐67 is a chromatin‐associated protein with a dynamic distribution pattern throughout the cell cycle and is thought to be involved in chromatin organization. The lack of genomic interaction maps has hampered a detailed understanding of its roles, particularly during interphase. By pA‐DamID mapping in human cell lines, we find that Ki‐67 associates with large genomic domains that overlap mostly with late‐replicating regions. Early in interphase, when Ki‐67 is present in pre‐nucleolar bodies, it interacts with these domains on all chromosomes. However, later in interphase, when Ki‐67 is confined to nucleoli, it shows a striking shift toward small chromosomes. Nucleolar perturbations indicate that these cell cycle dynamics correspond to nucleolar maturation during interphase, and suggest that nucleolar sequestration of Ki‐67 limits its interactions with larger chromosomes. Furthermore, we demonstrate that Ki‐67 does not detectably control chromatin‐chromatin interactions during interphase, but it competes with the nuclear lamina for interaction with late‐replicating DNA, and it controls replication timing of (peri)centromeric regions. Together, these results reveal a highly dynamic choreography of genome interactions and roles for Ki‐67 in heterochromatin organization. Synopsis: pA‐DamID mapping and perturbation experiments reveal that Ki‐67 interacts in interphase with late‐replicating genomic regions in pre‐nucleolar bodies and in nucleoli, in competition with the nuclear lamina. The results uncover roles for Ki‐67 in nuclear organisation and control of replication timing. pA‐DamID maps reveal genome‐wide interaction patterns of Ki‐67 in interphase. Ki‐67 interacts with late‐replicating genomic regions in pre‐nucleolar bodies and in nucleoli. Ki‐67 controls replication timing of centromeric regions. Abstract : pA‐DamID mapping and perturbation experiments reveal that Ki‐67 interacts in interphase with late‐replicating genomic regions in pre‐nucleolar bodies and in nucleoli, in competition with the nuclear lamina. The results uncover roles for Ki‐67 in nuclear organisation and control of replication timing.